Patriarchy and Greekness: Michael Cacoyannis’ Realism in the Girl in Black [To koritsi me ta mavra] (1956) - Potamias, Spyridon (Zeitschrift für Balkanologie, 2025)
The present text attempts to highlight how Michael Cacoyannis, in dialog with both the Generation of the 1930s and the 19th-century tradition of European realism, adopted the aesthetic categories (particular, typical, catharsis, etc.) present in the Girl in Black. The archetypal phenomenon of patriarchy in the Greek countryside of the 1950s and its effects on everyday life are examined in this article. Furthermore, Cacoyannis’ concept of Greekness is differentiated from the way the Generation of the 1930s conceived the concept, giving prominence to the movie’s realistic character.